The Influence of Entrepreneurship Knowledge and Use of Social Media on Entrepreneurial Interest of FKIP Students at Riau University - Rena Agustina; Sumarno Sumarno; Yogi Riyantama (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is a type of quantitative descriptive research which aims to determine the influence of entrepreneurial knowledge and the use of social media on the interest in entrepreneurship of Riau University FKIP students. The population in this study was 1,404 students, with a sample of 93 students. This research uses secondary data and primary data. Secondary data was obtained through entrepreneurship course grades, while primary data was obtained through questionnaires. Data analysis uses descriptive analysis and multiple linear regression. The research results show that entrepreneurial knowledge and the use of social media have a positive and significant effect on the entrepreneurial interest of FKIP Riau University students with a coefficient of determination (R2) of 68.1% at a significance level smaller than 0.05, namely 0.000. This shows that the better the entrepreneurial knowledge obtained, the greater the student's interest in entrepreneurship and the greater the use of social media, the greater the interest in entrepreneurship of FKIP University of Riau students.